Tindak Tutur Ekspresif dalam Novel Partikel karya Dee Lestari - Anoza Citra Paramita; Ngusman Abdul Manaf (Persona: Kajian Bahasa dan Sastra, 2023)
The aim of the research was to analyze the types of expressive speech acts and the context of using speech strategies in expressive speech acts in the novel Particle by Dee Lestari. The research method is descriptive qualitative. The source of the data in this research is the dialogue of characters indicating expressive speech acts in the novel Particle by Dee Lestari. Data collection techniques were carried out using two techniques, namely reading and taking notes. After that, identification of the data included in the types of expressive speech acts and the context of the use of speech strategies were carried out. The results of this study indicate that there are 10 types of expressive speech acts, namely congratulating, praising, thanking, apologizing, expressing pleasure, expressing anger, satirizing, insulting, criticizing, and complaining. The dominant expressive speech act in the research is congratulating. In the context of the use of speech strategies used in the novel Particle by Dee Lestari, namely in the context of speakers (-K+S) using a lot of speech strategies (SBTTBKP, SBTTBKN, SBTBB, and SBSS); in the context of speakers (=K+S) many use speech strategies (SBTTBKP); in the context of speakers (+K+S) using a lot of speech strategies (SBTTBKP); in the context of speakers (+K-S) use a lot (SBTTBKP); in the context of speakers (=K-S) use a lot of (SBTTBKP); in the context of dominant (-K-S) speakers (SBTTBKP).